The Drosophila melanogaster transcriptome by paired-end RNA sequencing - Daines, Bryce; Wang, Hui; Wang, Liguo; Li, Yumei; Han, Yi; Emmert, David; Gelbart, William; Wang, Xia; Li, Wei; Gibbs, Richard; Chen, Rui (Genome Research, 2011)
RNA-seq was used to generate an extensive map of the Drosophila melanogaster transcriptome by broad sampling of 10 developmental stages. In total, 142.2 million uniquely mapped 64–100-bp paired-end reads were generated on the Illumina GA II yielding 356× sequencing coverage. More than 95% of FlyBase genes and 90% of splicing junctions were observed. Modifications to 30% of FlyBase gene models were made by extension of untranslated regions, inclusion of novel exons, and identification of novel splicing events. A total of 319 novel transcripts were identified, representing a 2% increase over the current annotation. Alternate splicing was observed in 31% of D. melanogaster genes, a 38% increase over previous estimations, but significantly less than that observed in higher organisms. Much of this splicing is subtle such as tandem alternate splice sites.
10.1101/gr.107854.110